Niger : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper takes stock of Niger's tools to directly and indirectly combat corruption and shows that shortcomings in public-sector governance take a toll on private-sector development, especially young firms and exporters. Measures to advance Niger's anticorruption agenda are laid out. This paper describes Niger's anti-corruption framework, discusses how broader public-sector governance reforms can contribute to curbing corruption, assesses the impact on the private sector, and suggests measures to advance anticorruption reforms. The authorities profess commitment to fight corruption and have taken steps to revamp the anti-corruption framework. Niger is also equipped with legal and regulatory audit bodies that contribute to combatting corruption and promoting good governance. Although the legal and regulatory framework for public procurement is sound, its effective implementation remains elusive. Recent progress in simplifying administrative procedures should discourage public officials from exploiting complex bureaucracy to extract bribes. Formal regression analysis confirms that firms subject to corruption record lower sales and productivity growth relative to those that do not pay bribe.